Digital Marketing in Fashion Industry - Patil, Kanchan; Khathuria, Dheeraj (Indian Journal of Computer Science, 2020)
In todayâ€™s world digital marketing is growing at an exponential rate with no stopping at all. With websites and apps like Facebook, Instagram, Snapchat, YouTube, etc., the industry of media engagement is dominating the world. As we see through Facebook and watch YouTube, we don’t really understand what is happening there. Your mind instantly goes on an auto-pilot mode and starts believing whatever is shown on the feeds of Instagram and Facebook. An average user takes it in, but does not necessarily understand the message or the mind does not question whether the information is true or not. Behavioural/phycological targeting is another aspect which takes huge advantage of big data as well as data analytics to influence the minds of the users. In this research, there would be a comprehensive analysis of how digital marketing is influencing or manipulating the behaviour/minds of a normal user/data consumer. This research would be concentrating on the biggest social media platforms to understand how the â€˜ad industryâ€™ of these media work and what are the drivers behind it.